PENGARUH JANGKA PENDEK DAN JANGKA PANJANG PERUBAHAN SUKU BUNGA DAN KURS RUPIAH TERHADAP HARGA SAHAM: STUDI EMPIRIS DI INDONESIA (2000:1 â 2010:4) - Maryatmo, Rogatianus (Semarang State University, 2010)
The present study investigates the role of exchange rate and interest rate in stock price discovery inIndonesia.Indonesiais experiencing a kind of bubble which is indicated by surplus of current account accompanied by high capital inflow. Capital inflow simustaneusly influences exchange rate, and interest rate, and thus sequently affects stock prices. Employing cointegration approach and Engle Granger Error Corection Model (ECM), covering monthly time series data from January 2000 to April 2010, both short run and long run relationships are investigated. It is found out that there is cointegration relationship between stock price as dependent variable and Â exchange rate Â and interest rate, as independent variables. In the long run and in the short run, interest rate statisticaly significant negatively influences the stock prices. The impact of exchange rate on stock price is statistically significant, and changes in sign from negative in the short run effect to positive in the long run effect. In the long run, stock price is elastic to the changes in interest rate, and exchange rate. In the short run, the elasticity of stock price is decreasing in responding to the change in interest rate and exchange rate.Â